2020
DOI: 10.22541/au.159188231.19236328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 lockdown on admission to gynecological emergency departments: results from a multicenter Italian study

Abstract: Objective: To evaluate the impact of COVID-19 lockdown on admissions to gynecological emergency departments (ED). Design: Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
2
8
1
Order By: Relevance
“…The main result of our study was that total ER admissions in 2020 decreased by 81%. Our results are similar to previous studies that have demonstrated the same trend in both child and adult patients [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. We can speculate that social-distancing measures, the use of face masks, hand washing, and the complete closure of social activities may have contributed not only to the reduction of SARS-CoV-2 diffusion [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] but also to the reduction of the spread of other diseases, particularly of acute communicable diseases, as confirmed in a recent study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…The main result of our study was that total ER admissions in 2020 decreased by 81%. Our results are similar to previous studies that have demonstrated the same trend in both child and adult patients [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. We can speculate that social-distancing measures, the use of face masks, hand washing, and the complete closure of social activities may have contributed not only to the reduction of SARS-CoV-2 diffusion [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] but also to the reduction of the spread of other diseases, particularly of acute communicable diseases, as confirmed in a recent study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although, many studies have noted a significant decline in emergency admissions. 3 , 4 , 5 This suggests that patients at admission would present worse conditions than those in the previous year, which our research contradicts.…”
contrasting
confidence: 69%
“…Concerns about late presentation to care during the COVID-19 pandemic have been described in numerous specialties, including surgery, cardiology, and pediatrics, raising concerns that a worrying trend is emerging. 4 13 Our data suggest that women may be delaying care owing to concerns about COVID-19 exposure and presenting in more critical condition. Although it is important to continue to encourage the public to practice social distancing measures, it is equally important to encourage patients to present for care if they experience worrying symptoms.…”
Section: Discussionmentioning
confidence: 88%